Analisis nilai-nilai toleransi peserta didik kelas V di Sekolah Dasar - Nugroho, Rizki Dwi; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2026)
This study aims to describe the values of tolerance towards all forms of diversity in upper grade students in an inclusive elementary school. The value of tolerance is a form of understanding and acceptance of differences in everyday life. The research method used in this study is a qualitative method, data collection techniques through interviews, observations and questionnaires, analysis using the interactive model analysis of Miles and Huberman. Based on the results of the research analysis, the indicators used in the study show that most fifth grade students of Al Firdaus Elementary School have a very high tolerance category. The form of high tolerance values is seen in students who do not discriminate against friends, respect and appreciate diversity, on the other hand, teachers also play a role as facilitators and good role models and with the support of good communication between the school and parents of students. The results of this study are an indicator that fifth grade students at Al Firdaus Elementary School have good knowledge and education about the value of tolerance, so that students can apply the value of tolerance in everyday life, both in the school environment and the community environment.